What is a good man? A qualitative field study of how hegemonic masculinity is changing and being maintained in relation to livelihood diversification, education and gendered division of labour in Southern Ethiopia - Hambleton,Astrid Thea (2016)
Gender equality has become a top priority worldwide. However, gender tends to be synonymous with women and the agency of men is too often marginalised in both development interventions and research. Previous studies have found that as men are not included in the Gender and Development paradigm a “crisis of masculinity” is occurring which implies that sustainable gender equality will be more difficult to achieve. This thesis examines how hegemonic masculinity is changing and being maintained in relation to livelihood diversification, gendered division of labour and education. The findings are based on 35 semi-structured interviews with individuals living in two peri-urban villages in Southern Ethiopia. The study finds that hegemonic masculinity in this location is changing. The practice of hegemonic masculinity has shifted from being a good farmer to attaining education, as livelihoods diversify. The introduction of education is also changing hegemonic masculinity to become more compatible with gender equality. Finally, the study concludes that core hegemonic masculinity ideals, including the male breadwinner norm and the gendered division of labour (implying that men do not engage in female coded reproductive labour without being emasculated), are being maintained. This implies that as livelihoods are diversified, men’s ability to practise hegemonic masculinity increasingly depends on access to resources.
Keywords: Hegemonic masculinity; Ethiopia; Diversification of Livelihoods; Gendered Division of Labour; Education and Masculinity